FINANCIAL PERFORMANCE COMPARATIVE ANALYSIS BETWEEN CONSUMER GOODS AND REAL-ESTATE COMPANIES BEFORE AND DURING THE COVID-19 PANDEMIC - Latie, Geraldo Erlan; Suhendah, Rousilita (Graduate Program of Universitas Tarumanagara, 2023)
This research aims to determine the difference in financial performance of consumer goods and real estate companies prior to and during COVID-19 outbreaks. The research period starts from December 2019 (prior to the COVID-19 outbreaks) and ends in December 2020 (during the COVID-19 outbreaks). The research design used in this study is descriptive research with purposive sampling methods. The total samples used in this study were 146 samples, processed using the Microsoft Excel and Statistical Package for the Social Sciences (SPSS) ver.26 software. This research used the Wilcoxon Signed Rank Test as its research model. The result of this research shows that there is a significant difference in the aspect of profitability, while in the aspect of liquidity and solvability, no significant difference was found between prior to the pandemic (2019) and during the pandemic (2020).